2016
DOI: 10.3389/fpsyg.2016.01790
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Ambiguity in Information Seeking: Eye Gaze Patterns Reveal Contextual Behavior in Dealing with Uncertainty

Abstract: Information foraging connects optimal foraging theory in ecology with how humans search for information. The theory suggests that, following an information scent, the information seeker must optimize the tradeoff between exploration by repeated steps in the search space vs. exploitation, using the resources encountered. We conjecture that this tradeoff characterizes how a user deals with uncertainty and its two aspects, risk and ambiguity in economic theory. Risk is related to the perceived quality of the actu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 58 publications
(60 reference statements)
0
27
0
Order By: Relevance
“…These features are then used for statistical inferences, classification, and prediction. For instance, some variants of aggregated fixation-count and fixation-duration were used in studies reported in [14,15,19,21,39,41,59,63]. Eye-dwell time and/or visit time was used by Fahey et al [14].…”
Section: Related Work 21 Information Relevance and Eye-trackingmentioning
confidence: 99%
“…These features are then used for statistical inferences, classification, and prediction. For instance, some variants of aggregated fixation-count and fixation-duration were used in studies reported in [14,15,19,21,39,41,59,63]. Eye-dwell time and/or visit time was used by Fahey et al [14].…”
Section: Related Work 21 Information Relevance and Eye-trackingmentioning
confidence: 99%
“…For instance, sections and their associated features in search engine results can be considered patches. From a foraging perspective in image search, the searcher is the predator (or forager [38]), the information patch is any segment or a region within an image (or image itself) in a given information environment. The piece of information a user is looking for is the prey, and the consumed (or gained) information is the information diet.…”
Section: Query Suggestion In Image Searchmentioning
confidence: 99%
“…Decision making under uncertainty is what our brain does most of the time, whereas situations of known risk are relatively rare and found mostly in gambling. Recently, decisions under Knightian uncertainty have received increasingly more attention (Al-Najjar & Weinstein, 2015;Feldman Hall, Glimcher, Baker, & Phelps, 2016;Keskin, 2017;Wittek, Liu, Darányi, Gedeon, & Lim, 2016), motivated by the gap between observed behavior and the predicted outcome of models. Therefore, introducing uncertainty into the basic theory would bring the model closer to the natural state.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, authors have directly introduced prospect theory into studies of consumer behavior under uncertainty, where the results deviate from traditional behavioral theory, especially the large biases in the cognitive process (Prokosheva, 2016;Volz & Gigerenzer, 2012). Some studies have also stated that ignoring or simplifying information-based decisions cannot be considered optimal (Wittek et al, 2016). Some recent studies have proposed and verified that the Bayesian learning method is an appropriate method for addressing Knightian uncertainty (Aadland, Caplan, & Phillips, 2007;Al-Najjar & Weinstein, 2015;Vilares & Kording, 2011).…”
Section: Introductionmentioning
confidence: 99%